2015
DOI: 10.15388/informatica.2015.51
|View full text |Cite
|
Sign up to set email alerts
|

Extension of the ARAS Method for Decision-Making Problems with Interval-Valued Triangular Fuzzy Numbers

Abstract: This paper proposes an extension of the ARAS method which, due to the use of intervalvalued fuzzy numbers, can be more appropriate for solving real-world problems. In order to overcome the complexity of real-world decision-making problems, the proposed extension also includes the use of linguistic variables and a group decision making approach. In order to highlight the proposed methodology an example of a faculty websites evaluation is considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 54 publications
0
69
0
2
Order By: Relevance
“…Zavadskas et al [36] suggested a novel extension of the MULTIMOORA method by combining interval-valued intuitionistic fuzzy terms. Stanujkic et al [37] suggested the extended MULTIMOORA approach based on a triangular fuzzy data set in order to solve a communication circuits design selection problem. Awasthi and Baležentis [38] presented a combinative methodology using BOCR criteria integrated with F-MULTIMOORA approach based on a Monte Carlo simulation sensitivity analysis, in order to determine the robustness of the proposed method to variation in criterion and decision-maker weights in a logistics service provider selection.…”
Section: Introductionmentioning
confidence: 99%
“…Zavadskas et al [36] suggested a novel extension of the MULTIMOORA method by combining interval-valued intuitionistic fuzzy terms. Stanujkic et al [37] suggested the extended MULTIMOORA approach based on a triangular fuzzy data set in order to solve a communication circuits design selection problem. Awasthi and Baležentis [38] presented a combinative methodology using BOCR criteria integrated with F-MULTIMOORA approach based on a Monte Carlo simulation sensitivity analysis, in order to determine the robustness of the proposed method to variation in criterion and decision-maker weights in a logistics service provider selection.…”
Section: Introductionmentioning
confidence: 99%
“…First, this review is focused on the use of the MCDM utility determining approaches rather than the old MCDM techniques. WASPAS and SWARA methods [225] can be adapted to the development of hybrid MCDM meth- ods such as ARAS, EDAS [226][227][228][229], Investment Value Assessments along with Recommendations (INVAR) [230], CODAS [231,232], Fuzzy Ranking and Aggregated Weights (AFRAW) [233], MULTI-MOORA and MOORA [234][235][236][237][238]. The concept of the neutrosophic set developed by Smarandache is a set model which generalizes the classic set, fuzzy set, interval fuzzy set, intuitionistic fuzzy set and interval valued intuitionistic fuzzy set.…”
Section: Resultsmentioning
confidence: 99%
“…ARAS decision making technique is identified as one of the newest among all MCDM methods. Despite this fact, ARAS was put in application to solve different decision making problems (Stanujkic, 2015). A.…”
Section: Discussionmentioning
confidence: 99%
“…Ozbek and E. Erol (2017) also acknowledge wide use of ARAS method and its effective application to solve problems like location choice for logistics centers, energy generation methods' choice, waste dump site selection and other. (Ozbek & Erol, 2017) According to D. Stanujkic (2015) even though ARAS technique enables to solve a lot of decision making problems, application of interval-valued fuzzy numbers could extend use of ARAS even further.…”
Section: Discussionmentioning
confidence: 99%